Kendala dan Upaya Dalam Pembelajaran IPS Terpadu Kelas VIII di SMP Pertiwi Siteba Kecamatan Nanggalo Kota Padang. - Winanda, Egia - (STKIP PGRI Sumbar, 2014)
This research was conducted with the aim of observing and analyzing constraints and effort in learning social studies in junior high eighth grade Integrated Earth Siteba subdistrict Nanggalo Padang.The research is a qualitative, informants were taken with Snow-ball sampling technique, the research informants contacted in sequence. Data collection techniques are interviews, observations, field recording, and shooting.Results showed (1) Constraints faced junior high school students in the face of Earth Siteba Integrated Social learning is a teaching of this Combined Geography, Sociology, History, Economics. Teachers who teach only the departments of geography, so that teachers often lack an understanding of the lesson. Judging from the lack of external infrastructure. Judging from the internal lazy student learning. (2) Efforts made in Integrated Social learning is diverse, made either students or teachers and principals, they try to make the students help each other learn. Teachers need to be very learned once and principals provide complete facilities such as internet service once students for the Integrated Social learning, so that students can understand the Integrated Social learning.